2016
DOI: 10.1186/s13068-016-0484-3
|View full text |Cite
|
Sign up to set email alerts
|

Using the β-glucosidase catalyzed reaction product glucose to improve the ionic liquid tolerance of β-glucosidases

Abstract: BackgroundPretreating biomass with ionic liquids (IL) increases enzyme accessibility and cellulose is typically recovered through precipitation with an anti-solvent. An industrially feasible pretreatment and hydrolysis process requires robust cellulases that are stable and active in the presence of either small amounts of ILs co-precipitated with recovered cellulose or for saccharifications in the presence of IL. β-glucosidase (BG) hydrolyzes cellobiose into two molecules of glucose (Glc) and is the last step … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
46
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 45 publications
(50 citation statements)
references
References 48 publications
4
46
0
Order By: Relevance
“…The double and triple mutant containing V169C mutation was highly active, together the V169C/E173L/I246A had the highest increase in residual specific activity, almost 1.9-folder higher at 1 M glucose, compared to wild-type (Supplementary file, Table S3) and (Fig. 5b) These observations are in line with our previous reports when we showed that the β-glucosidase reaction product glucose improved the half-life and the kinetic stability of β-glucosidase, H0HC94 [22] and O08324 [15]. B8CYA8 and all its mutants show elevated melting temperature (Supplementary file, Table S4) with increasing concentrations of glucose, as reported previously [15, 22].…”
Section: Resultssupporting
confidence: 90%
See 4 more Smart Citations
“…The double and triple mutant containing V169C mutation was highly active, together the V169C/E173L/I246A had the highest increase in residual specific activity, almost 1.9-folder higher at 1 M glucose, compared to wild-type (Supplementary file, Table S3) and (Fig. 5b) These observations are in line with our previous reports when we showed that the β-glucosidase reaction product glucose improved the half-life and the kinetic stability of β-glucosidase, H0HC94 [22] and O08324 [15]. B8CYA8 and all its mutants show elevated melting temperature (Supplementary file, Table S4) with increasing concentrations of glucose, as reported previously [15, 22].…”
Section: Resultssupporting
confidence: 90%
“…5b) These observations are in line with our previous reports when we showed that the β-glucosidase reaction product glucose improved the half-life and the kinetic stability of β-glucosidase, H0HC94 [22] and O08324 [15]. B8CYA8 and all its mutants show elevated melting temperature (Supplementary file, Table S4) with increasing concentrations of glucose, as reported previously [15, 22]. The increase was about 4-5 °C in the presence of the 0.5 M glucose, and 6-7 °C in 1 M glucose (Supplementary file, Table S4), and indicated the benefits of glucose accumulation during large-scale high biomass loading saccharification reactions.…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations